2020
DOI: 10.1029/2019jd031226
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences of Chemical Composition and Optical Properties of Aerosols in the Tibetan Plateau

Abstract: In this study, PM 2.5 filter samples were collected from two high-elevation sites located in the southern and northern areas of Tibetan Plateau (TP): the Qomolangma Station for Atmospheric Environmental Observation and Research (QOMS) and Waliguan Baseline Observatory (WLG), respectively. Collected samples were analyzed to examine the regional differences in aerosol properties and relate them to potential chemical processes in the TP area. The aerosol mass concentrations inferred from measured chemical compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 51 publications
5
39
0
Order By: Relevance
“…Waliguan, Gongga, Lhasa, and Mt. Yulong (Cong et al., 2015; Kang et al., 2016; Wan et al., 2016; Xu et al., 2020; Zhang et al., 2001, 2012; Zhao et al., 2013). Chemical characterization of submicron aerosols has also been carried out by using aerosol mass spectrometer at a few sites such as Menyuan (Du et al., 2015), Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Waliguan, Gongga, Lhasa, and Mt. Yulong (Cong et al., 2015; Kang et al., 2016; Wan et al., 2016; Xu et al., 2020; Zhang et al., 2001, 2012; Zhao et al., 2013). Chemical characterization of submicron aerosols has also been carried out by using aerosol mass spectrometer at a few sites such as Menyuan (Du et al., 2015), Mt.…”
Section: Introductionmentioning
confidence: 99%
“…2018; Yan et al, 2015a). For example, a model study showed that BrC contributes up to +0.25 W m −2 of radiative forcing on a planetary scale, which is approximately 19 % of the absorption by anthropogenic aerosols (Feng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al. (2020) also found a distinctly higher light absorption efficiency of BrC at QOMS than at Waliguan through water extraction of filter samples collected during these two studies. The B abs,370 at QOMS was comparable with that (15.0 Mm −1 ) measured at Lulang, one remote site located on the southeastern TP, but much lower than that (53.0 Mm −1 , Table 1) measured at an urban site in Lhasa (Zhu et al., 2017).…”
Section: Resultsmentioning
confidence: 71%
“…The campaign‐averaged B abs,BrC at 370 nm (B abs,BrC,370 ) was 4.4, 0.6, and 0.7 Mm −1 for QOMS, Waliguan, and NamCo, which contributed 33.1%, 22.4%, and 21.3% of the total light absorption at 370 nm, respectively. Similar to the total light absorption, the B abs,BrC,370 at NamCo and Waliguan was extremely low, which might be caused by the low aerosol mass loading at NamCo or the limited abundance of light‐absorbing matter at Waliguan (Xu et al., 2020). In contrast, the relatively higher B abs,BrC,370 and the higher BrC contribution at QOMS might be attributed to the important contribution of light‐absorbing matter from the transported biomass burning emissions (An et al., 2019; Xu et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation